A COMPARATIVE ANALYSIS OF THE MANDATORY RULE DOCTRINE AND ITS APPLICATION IN THE SOUTH AFRICAN LABOUR COURT (The Pretoria Student Law Review, 2021)
Inherent in any employment relationship is the imbalance of bargaining power between the parties to the employment contract. On a globalised scale, this imbalance is exacerbated where employees are often reliant on the provisions within their contract to ensure they are adequately protected. Party autonomy enables the parties to choose the legal system that will govern these provisions and the employment relationship as a whole. The doctrine of mandatory rules purports to make applicable those ‘laws of a strictly positive, imperative nature’ so as to guarantee the protection of employees’ interests where party autonomy serves to conceal the power imbalance within the employment relationship. The Labour Court has, however, often misunderstood and neglected to consider the application of private international law rules, which are inclusive of the mandatory rule doctrine. The aim of this article is, therefore, to critically analyse the doctrine and question whether, from a comparative perspective, South African labour law can be considered as fitting within this framework as developed within the European Union and the United States, so as to ensure its protective elements are applied in the appropriate instances.
Keywords: mandatory rule doctrine; Labour Court; employment relationships; party autonomy; private international law